Factors Influencing Consumer Acceptance of Mobile Payment during the COVID-19 Pandemic & Usage Continuance Intent: A Quantitative Study - Syed Faizan Hussain Zaidi; Omar Ali; Marsela Thanasi-Boçe (Emerging Science Journal, 2023)
The presence of COVID-19 has transformed the business sector’s paradigm and prompted a speedy consumption of mobile payment software systems of diverse ranges. Corporate sectors and businesses across the globe brought a shift to offer mobile payment methods; consequently, consumers were urged to maximize the use of mobile payment throughout the pandemic. The present research aims to investigate the factors that might influence consumers' intent to accept mobile payments and their relationships during COVID-19. The technology adoption model and the unified theory of acceptance and use of technology were employed in this proposed mobile payment adoption framework. A quantitative research approach was identified as a suitable method for this research. An online survey was administered, and 304 participants responded to the questionnaire. The results of the data analysis revealed statistically significant relationships and a positive impact of the factors perceived performance, social influence, consumers’ satisfaction, and perceived usefulness on consumers’ usage continuation intention. However, the results identified that factors such as transaction risk didn’t affect perceived usefulness, and financial transaction transparency didn’t affect consumers’ usage intention. This study makes a substantial contribution to the consumers’ technology acceptance literature in terms of validating a proposed theoretical framework that highlights the factors that influence consumers’ mobile payment usage intentions. As this study was conducted at a later stage of the COVID-19 pandemic, it adds value to the existing literature by providing insights to business managers on the factors influencing mobile payment usage. Considering the practical perspective, this study offers evidence of the essential elements that mobile payment service designers and marketers should consider. Doi: 10.28991/ESJ-2023-07-05-07 Full Text: PDF